Spillover Effect Analysis of Economic Growth between Regency City in Jambi ProvinceCity - Berlian, Salshabila; Sumanto, Agus; Dwiputri, Inayati Nuraini (Journal of Applied Business, Taxation and Economics Research, 2025)
The goal of this research is to ascertain how spatial relationships between regions function, what areas help each region individually, and how Jambi City has spillover effects to other locations within Jambi Province. The methods employed were Moran Scatterplot, Moran Index, Local Indicator of Spatial Autocorrelation (LISA), and overlay analysis. The findings demonstrate that there is a clustering pattern for areas with comparable features and that all of the regencies and cities in the province of Jambi have an overall positive autocorrelation. Two cluster patterns have been identified in the eastern region, according to the LISA study. Muaro Jambi Regency and East Tanjung Jabung Regency fall into the high-high group, whereas Kerinci Regency falls into the low-low category. In Bungo Regency, Jambi City, Sungai Penuh City, Kerinci Regency, and Sarolangun Regency, on the other hand, the construction sector is the predominant growing sector and enjoys a comparative advantage, according to the overlay analysis results. In contrast, Bungo, Tebo, Sarolangun, and Kota Sungai Penuh are less affected by the processing sector.